IDENTIFYING ENGLISH – INDONESIAN SUBTITLES TRANSLATION TECHNIQUES OF SUBTITLES IN “INCREDIBLES 2” MOVIE - Najiha, Siti; Dahnilsyah, Dahnilsyah; M. Syarfi, M. Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The objective of this research is to identify the frequent translation techniques used by the translator in